2009
DOI: 10.1016/j.ijsu.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Does sildenafil reverse the adverse effects of ischemia on ischemic colon anastomosis: Yes, ‘no’

Abstract: Our results showed that 10mg/kg sildenafil decreased the adverse effects of ischemia on the healing of ischemic left colon anastomosis. Additional investigations are needed to confirm the effects of phosphodiesterase-5 inhibitors in ischemic colon anastomosis models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…A dose of 10 mg/kg sildenafil achieves possible systemic protective effects in rats. Higher doses (over 20 mg/kg) may have greater vasodilatatory effects but they may also have side effects such as hypotension, diminished tissue perfusion, and excessive anti-inflammatory response, whereas doses lower than 10 mg/kg is less or not effective at all [23,24]. For this reason, we chose to administer sildenafil as a single daily dose of 10 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…A dose of 10 mg/kg sildenafil achieves possible systemic protective effects in rats. Higher doses (over 20 mg/kg) may have greater vasodilatatory effects but they may also have side effects such as hypotension, diminished tissue perfusion, and excessive anti-inflammatory response, whereas doses lower than 10 mg/kg is less or not effective at all [23,24]. For this reason, we chose to administer sildenafil as a single daily dose of 10 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…In groups 1, 2 and 3, a colon segment of 1-, 2-and 3-cm long, respectively, underwent selective devascularization, as previously described by Griffen24. This method consists of devascularization of the marginal artery at two points, as well as the vasa recti located in-between, using a bipolar cautery 1 . At the midpoint of the devascularized segment, the colon was sectioned and an anastomosis was performed in the same way as described in control group.…”
Section: Anesthesia and Surgical Proceduresmentioning
confidence: 99%
“…Surgeries that require anastomosis of the large bowel are among the most commonly performed abdominal procedures in the western world 1 . Ongoing advances in terms of perioperative care and surgical techniques have provided better results in the surgical treatment of patients with colorectal diseases.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent laboratory studies demonstrated successful effects of PDE V inhibitors on cardioprotection after ischemia reperfusion injury [4,5] , as well as in ischemic injury of other organs, such as the colon, liver, and brain [6,7] . Deibert et al 8] revealed that vardenafil had increased portal flow and lowered portal pressure in patients with cirrhotic livers.…”
Section: Introductionmentioning
confidence: 99%